Correlation between Facial Soft Tissues and Vertical Facial Pattern in 12-16 Years Old Untreated Patients - Mamoona Batool, Ayesha Ashraf, Sarah Mahmood Mirza, Farhana Ashraf, Muhammad Azeem, Muhammad Imtiaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Soft tissue paradigm shift has accentuated significance of soft tissue variables in diagnosis & treatment planning. Aim: To find a correlation between facial soft tissues and underlying vertical facial patterns in young untreated patients. Methods: The lateral cephalograms of 170 young individuals were divided into three equal groups, i.e., long, average, and short face, in accordance with the vertical facial patterns. This was done using a cross-sectional research design. Upper and lower lip lengths and extent of lip protrusion were measured for each individual. Non-probability consecutive sampling was done. The relationship between face soft tissue and the vertical facial pattern was examined using the Pearson Correlation test and less than 0.05 p-value was held statistically significant. Result: Significant correlation between upper and lower lip lengths and vertical facial form was found. Similarly significant positive correlation between protrusion of upper and lower lips and vertical facial pattern was found. Conclusion: Cephalometric analyses suggest the vertical dimensions of facial soft tissues conform to the vertical skeletal patterns. The long facial patterns have increased lip lengths and procumbent lips. MeSH words: Cephalometric analysis, Cross-sectional study, Vertical facial pattern, Lip length